Stabling effects on equine respiratory tract using two different types of stable beds and pasture - Calciolari, K. [UNESP]; Gravena, K. [UNESP]; Bernardi, N. S. [UNESP]; Queiroz, D. J. [UNESP]; Lacerda Neto, J. C. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
Respiratory system affections in horses are the second cause of decrease in performance and removal from the sport or farm work, which are behind only the musculoskeletal disorders. Stabling and hay feeding predisposes horses' airways to inhalation of large numbers of irritating agents. To evaluate the influence of bed types used in bays, 3 groups of 5 horses each were studied for 45 days. Two groups were kept in stables with different wood beds - based rafters (autoclaved pine - MA and sawdust - SE) and the third group remained in the pasture. Biweekly evaluations with physical examination, hemogram, hemogasometry and bronchoalveolar lavage were performed. On physical examination, the presence of cough and sneezing was observed in animals of the SE group. In the bronchoalveolar lavage, the total nucleated cell count presented higher values in the animals in the pasture, followed by the SE group and finally the MA. It was concluded that the different beds used presented no difference with respect to the irritative capacity of the upper airways.
Keywords: horses; bronchoalveolar lavage; shavings; sawdust; allergy